Aruṇa-bhāratī : Professor A.N. Jani felicitation volume : essays in contemporary Indological research - Jani, A. N. (Arunoday Natvarlal), 1921-; Datta, B.; Sharma, Umesh Chandra, 1946-; Vyas, Nitin J. (Professor A.N. Jani Felicitation Volume Committee, Oriental Institute ; Sole distributors, Viveka Publications, 1983)
Festschrift honoring Arunoday Natvarlal Jani, b. 1921, Sanskrit scholar; comprises papers on Indic studies.